The Purchase Decisions Analysis of Netflix Users in Indonesia - Rizqy Aziz Basuki; Cynthia Eddja (Sekolah Pascasarjana Universitas Brawijaya, 2022)
Indoor entertainment has experienced relatively high growth, especially during the COVID-19 pandemic. People are allocating more of their spending to paid subscription-based streaming services. One of the most widely used companies by Indonesians is Netflix. Netflix users in Indonesia continue to increase yearly, even though many competitors offer competitive prices. Netflix is constantly innovating and developing, improving the quality of its service and promoting in various media in various ways. The object of this study is Netflix in Indonesia, and the sample of this study is users who have used and purchased Netflix in Indonesia. The data collection method in this study was by collecting questionnaires through Google Forms with a total of 315 respondents. The data analysis technique used in this study is PLS-SEM using SmartPLS 3.3.3 and SPSS 26.0 for validity, reliability, and descriptive analysis. The results showed that the quality of service, price, and promotion positively and significantly affected the purchase decisions of Netflix users in Indonesia.